2000
DOI: 10.1074/jbc.275.3.1529
|View full text |Cite
|
Sign up to set email alerts
|

Chloroplast Oxa1p Homolog Albino3 Is Required for Post-translational Integration of the Light Harvesting Chlorophyll-binding Protein into Thylakoid Membranes

Abstract: Multiple sorting pathways operate in chloroplasts to localize proteins to the thylakoid membrane. The signal recognition particle (SRP) pathway in chloroplasts employs the function of a signal recognition particle (cpSRP) to target light harvesting chlorophyll-binding protein (LHCP) to the thylakoid membrane. In assays that reconstitute stroma-dependent LHCP integration in vitro, the stroma is replaceable by the addition of GTP, cpSRP, and an SRP receptor homolog, cpFtsY. Still lacking is an understanding of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
182
2
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 225 publications
(187 citation statements)
references
References 32 publications
2
182
2
1
Order By: Relevance
“…However, despite the correct D1 integration into the thylakoid membrane, assembly of D1 into the PSII RC of ac29 was less efficient as a result of the loss of Alb3.1p. This protein is the homolog of mitochondrial Oxa1p and of bacterial YidC, which have been described as integrases involved in the translocation and/or integration of membrane proteins (Moore et al, 2000(Moore et al, , 2003Kuhn et al, 2003). Nevertheless, it was reported that the integral membrane Cox3p and Pf3 coat protein integrate into membranes independently from Oxa1p and YidC, respectively, although with a lower integration efficiency (Hell et al, 2001;Serek et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, despite the correct D1 integration into the thylakoid membrane, assembly of D1 into the PSII RC of ac29 was less efficient as a result of the loss of Alb3.1p. This protein is the homolog of mitochondrial Oxa1p and of bacterial YidC, which have been described as integrases involved in the translocation and/or integration of membrane proteins (Moore et al, 2000(Moore et al, , 2003Kuhn et al, 2003). Nevertheless, it was reported that the integral membrane Cox3p and Pf3 coat protein integrate into membranes independently from Oxa1p and YidC, respectively, although with a lower integration efficiency (Hell et al, 2001;Serek et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…This pathway uses the stromal proteins cpSRP54 and cpSRP43, which bind as heterodimers or heterotrimers to the imported LHCPs forming the so-called transit complex. The membrane insertion of the LHCPs strictly requires cpFtsY, GTP, and the integral membrane protein Alb3 in vitro (Tu et al, 1999;Moore et al, 2000Moore et al, , 2003. However, disruption of the genes encoding cpSRP54 and cpSRP43 in Arabidopsis thaliana has only mild effects on the accumulation of LHCPs in comparison with the wild type, whereas the disruption of Alb3p leads to a loss of LHCPs (Sundberg et al, 1997;Tu et al, 1999;Hutin et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…They also provided valuable information on the physiology and regulation of chloroplast protein import. Furthermore, maize and Arabidopsis mutants defective in protein transport to the thylakoid also have been isolated (Voelker and Barkan, 1995; Voelker et al, 1997;Roy and Barkan, 1998;Amin et al, 1999;Moore et al, 2000). These mutants helped to further define the various pathways of transport to the thylakoid and even helped to uncover a new export pathway in Escherichia coli .…”
Section: Introductionmentioning
confidence: 99%
“…In Arabidopsis, ALB3 was shown to be essential for the assembly of the light-harvesting complex (LHC) in the thylakoid membrane (Moore et al, 2000). Mutants lacking ALB3 have an albino phenotype (Sundberg et al, 1997).…”
Section: Introductionmentioning
confidence: 99%